CREDO ORGANIZATIONAL CULTURE AND ORGANIZATIONAL COMMITMENT AS PREDICTORS OF JOB SATISFACTION AND INTENTION TO LEAVE - Siwi Ratna; Yupono Bagyo; Nunung Suzana Widiyanti; Sunarto Sunarto; Sonhaji Sonhaji (STIE Malangkucecwara, 2022)
This study aims to determine the effect of Credo Organizational Culture and Organizational Commitment on Intention to Leave with Job Satisfaction as a Mediation Variable at PT. Johnson & Johnson Indonesia, Medical Division.This type of research is survey research using a quantitative approach. The study population was the employees of PT. Johnson & Johnson Indonesia, especially in the Medical Division, which amounted to 70 employees, while the total sample was 60 respondents who were taken using the Slovin's equation. Data collection was carried out by means of a questionnaire. The data analysis technique used is Structural Equation Modeling (SEM) with Smart PLS (Partial Least Square) software.The results in this study indicate that: 1) Credo Organizational Culture has a positive and significant effect on Job Satisfaction. 2) Organizational Commitment has a positive and significant effect on Job Satisfaction, 3) Job Satisfaction has a negative and un significant effect on Intention to Leave (4) Credo Organizational Culture has a negative and significant effect on Intention to Leave (5) Organizational Commitment has a positive and significant effect on Intention to Leave. The results also show that organizational commitment is a variable that has a dominant effect on intention to leave. The findings of this study suggest that employees' high levels of commitment influence their desire to leave.